Pengembangan Profesionalitas Guru Pendidikan Agama Islam Di Sekolah Menengah Atas Primaganda Jombang - Solikhin; Ali Mustofa (Jurnal Pendidikan Islam, 2019)
Abstract: Teacher professionalism is very important. Moreover, PAI teachers, because the PAI teacher profession must be able to be a role model for students. The main task of the PAI teacher is to improve morals or morals, and instill faith and devotion in the hearts of students. Basically, PAI teachers at PRIMAGANDA Jombang High S chool gave positive thinking to their professional development through various methods carried out, both from within themselves such as quality development such as attending training and others. For example, the training that has been attended by PAI teach ers, namely the Subject Teachers' Conference (MGMP), meetings between high school teachers, attending work shops or upgrading conducted by the Minister of Education and Culture, Jombang. Such an attitude gives the view that the professionalism of a Muslim teacher is not just a teacher in educating his students, but people who are obliged to remind each other that as servants of God are obliged to carry out worship that has been outlined by Him to us. Supporting factors in the development of PAI teacher prof essionalism are support from school principals and Waka curriculum. In addition, adequate facilities and infrastructure, teacher welfare (salary increase) certification allowances and awards, while the inhibiting factors are lack of funding and less time i n learning PAI.